Acute caffeine supplementation offsets the impairment in 10-km running performance following one night of partial sleep deprivation: a randomized controlled crossover trial - Richard Metcalfe (European Journal of Applied Physiology, 2025)
Introduction: Whether acute caffeine supplementation can offset the negative effects of one-night of partial sleep deprivation (PSD) on endurance exercise performance is currently unknown. Methods: Ten healthy recreational male runners (age: 27 ± 6 years; V̇ O2 max : 61 ± 9 mL/kg/min) completed 4 trials in abalanced Latin square design, which were PSD + caffeine (PSD-Caf), PSD + placebo (PSD-Pla), normal sleep (NS) + caffeine (NS-Caf) and NS + placebo (NS-Pla). 3 and 8 h sleep windows were scheduled in PSD and NS, respectively. 10-km treadmill time trial (TT) performance was assessed 45 min after caffeine (6 mg/kg/body mass)/placebo supplementation in the morning following PSD/NS. Blood glucose, lactate, free fatty acid and glycerol were measured at pre-supplementation, pre-exercise and after exercise. Results: PSD resulted in compromised TT performance compared to NS in the placebo conditions by 5% (51.9 ± 7.7 vs.49.4 ± 6.9 min, p = 0.001). Caffeine improved TT performance compared to placebo following both PSD by 7.7% (PSD-Caf:47.9 ± 7.3 min vs. PSD-Pla: 51.9 ± 7.7 min, p = 0.007) and NS by 2.8% (NS-Caf: 48.0 ± 6.4 min vs. NS-Pla: 49.4 ± 6.9 min,p = 0.049). TT performance following PSD-Caf was not different from either NS-Pla or NS-Caf (p = 0.185 and p = 0.891,respectively). Blood glucose, lactate, and glycerol concentrations at post-exercise, as well as heart rate and the speed/RPE ratio during TT, were higher in caffeine trials compared to placebo. Conclusions: Caffeine supplementation offsets the negative effects of one-night PSD on 10-km running performance.